Respuesta :

Answer : option D

[tex]y^2 - 2x + 2y-5=0[/tex]

We apply completing the square method

Move all the y terms on one side

y^2 +2y = 2x + 5

In completing the square method , we take coefficient of y then divide it by 2  and square it

2/2 =1  then 1^2 = 1

Add it on both sides

[tex]y^2 + 2y +1 = 2x+5+1[/tex]

[tex] (y+1)^2= 2x+6[/tex]

[tex] (y+1)^2= 2(x+3)[/tex]

Solve for x

[tex] (y+1)^2= 2x+6[/tex]

[tex] 2x=(y+1)^2-6[/tex] (divide by 2 on both sides)

[tex] x=1/2(y+1)^2-3[/tex]

Vertex is (h,k) that is (-3,-1). h= -3  and k = -1

The value of a= 1/2

[tex]p = \frac{1}{4a}[/tex]

Plug in 1/2 for 'a'

so P = 1/2

Focus = (h+p, k)

h= -3  and k = -1, p = 1/2

[tex](-3+\frac{1}{2} , -1) = (\frac{-5}{2} , -1)[/tex]

Directrix x=(h - P)

[tex]x = -3 - \frac{1}{2} = \frac{-7}{2}[/tex]

Option D is correct






ACCESS MORE